Postharvest shelf life extension of Cucumber (Cucumis sativus) and Irish potato (Solanum tuberosum) using X-rays in Benue State, Nigeria - Akaagergera,Nguvan Becky -Isidore Komofor Ngongiaha-Alexander A. Tyovendaa-Soweh Raymond Mbinkonga-b,c, Kenkwa Basil Songwee- Rousinne Komofor Chetghof (University of Eloued جامعة الوادي, 2023)
This paper investigates the postharvest shelf life extension of cucumber and irish potato using X-rays, in Benue State, Nigeria. The selection of samples for the research was done from the traditional markets in Gboko for similar properties as depicted in the literature. For both products, six samples each with one kept as the control sample were X-ray irradiated with and of X-rays. An ambient storage temperature range of 27 – 30oC was recorded. The measured density, moisture content M.C (%), and pH were in the intervals: , , and for cucumber, and , , and for irish potato respectively. The percentage mass shrinkage ( ( )) of the control and 100 X-ray irradiated samples were: 45.0% and 31.6% for cucumber, and 23.8% and 20.5% for irish potato respectively. The mass shrinkage ( ) was found to increase during preservation and higher values extended the shelf life of the products. The of X-rays was effective in preserving cucumber for an additional 7 – 8 days and irish potato for additional 10 – 15 days of storage. In essence, cucumber and irish potato can be stored by exposure to specific values of diagnostic X-rays.
Article
Keywords: Cucumber; Irish potato; Physicochemical properties; Shelf Life; X-ray irradiation.